Endothelial progenitor cells accelerate endothelial regeneration in an in vitro model of Shigatoxin-2a-induced injury via soluble growth factors - Patry, Christian; Betzen, Christian; Fichtner, Alexander; Westhoff, Jens; Fleming, Thomas; Eckstein, Volker; Bruckner, Thomas; Hoffmann, Georg F.; Tönshoff, Burkhard; Rafat, Neysan (American journal of physiology. Renal physiology, 2018)
Endothelial injury with consecutive microangiopathy and endothelial dysfunction plays a central role in the pathogenesis of the postenteropathic hemolytic uremic syndrome (D + HUS). To identify new treatment strategies, we examined the regenerative potential of endothelial progenitor cells (EPCs) in an in vitro model of Shiga toxin (Stx) 2a-induced glomerular endothelial injury present in D + HUS and the mechanisms of EPC-triggered endothelial regeneration. We simulated the proinflammatory milieu present in D + HUS by priming human renal glomerular endothelial cells (HRGECs) with tumor necrosis factor-α before stimulation with Stx2a. This measure led to a time- and concentration-dependent decrease of HRGEC viability of human renal glomerular endothelial cells as detected by a colorimetric assay. Coincubation with EPCs (104-105 cells/ml) under dynamic flow conditions led to a significant improvement of cell viability in comparison to untreated monolayers (0.45 ± 0.06 vs. 0.16 ± 0.04, P = 0.003). A comparable regenerative effect of EPCs was observed in a coculture model using cell culture inserts (0.41 ± 0.05 vs. 0.16 ± 0.04, P = 0.003) associated with increased concentrations of vascular endothelial growth factor, insulin-like growth factor I, fibroblast growth factor-2, and hepatocyte growth factor in the supernatant. Treatment of Stx2a-injured monolayers with a combination of these growth factors imitated this effect. EPCs did not show distinct sings of migration and angiogenic tube formation in functional assays. These data demonstrate that EPCs significantly improve endothelial viability after Stx2a-induced injury in vitro and that this effect is associated with the release of growth factors by EPCs.